When dinosaurs die : a guide to understanding death - Brown, Laurene Krasny (Brown, Laurene Krasny. Dino life guides for families., 2009)
Explains in simple language the feelings people may have regarding the death of a loved one and the ways to honor the memory of someone who has died.